Methods for improving ductility of tungsten - A review. (September 2018) - Ren, Chai; Fang, Z.Zak; Koopman, Mark; Butler, Brady; Paramore, James; Middlemas, Scott
Abstract: Pure tungsten and tungsten alloys with minor alloying additions are known to be brittle at room temperature and have high ductile-to-brittle transition temperatures (DBTT). Improving the ductility of tungsten can have significant impact on both the manufacturing of and the range of applications of tungsten. Although there has been a significant volume of reported research on improving the ductility of tungsten over the span of several decades, it remains a difficult challenge. This is at least partially attributable to the fact that the understanding on the mechanical properties of tungsten and their dependence on microstructure has been insufficient. This article attempts to offer a critical review of the methods that have been reported in the literature for improving the ductility of tungsten in order to understand the critical factors that control the ductility (or lack thereof) in tungsten. It is clear from the literature that all tungsten materials that have been reported to be ductile at room temperature, or to have drastically reduced DBTT, are the result of thermomechanically processed (TMP) material with deformed and textured microstructures. Alloying tungsten with rhenium is essentially the only known method to improve the ductility of tungsten by alloying (excluding the class of alloys known as heavy alloys which are composites of tungsten with nickel and iron). Although there have been a large number of research reports in recent years on the effect of additives, including oxides, carbides, and others, the results are inconclusive to date or insignificant with respect to the effects of those additives on the ductility of tungsten independent of the effects of thermomechanical working. Using ultrafine-grained or nanocrystalline microstructure to improve the ductility of tungsten is another approach that has appeared promising. However, the results to date have not shown that the ductility of tungsten can be improved by reducing the grain size alone, without the benefits of thermomechanical processed or deformed microstructures. Another objective of this review is to examine the correlation between the ductility of tungsten and different microstructures resulting from different processing methods and compositions. Highlights: Review of methods that control and may yet improve the ductility of tungsten. All reported tungsten materials with room temperature ductility have been thermomechanically processed. Rhenium is the only known effective alloying element to improve the ductility of tungsten. No evidence has yet shown reducing grain size alone can improve the ductility of tungsten. Correlations are made between the microstructures and ductility of tungsten resulting from various methods and compositions.